(untitled) (Cadernos de Psicologia Social do Trabalho, 1999)
The Military Police of Espírito Santo has been going through transformations among which are found the creation of the Interactive Police and the inclusion of Total Quality Programs in the performance of services to the community. These changes produce effects on the life of the Military Police worker and need to be seen jointly with the current socio-economical and political situation of the Nation and of the State. In an attempt to grasp the effects of these transformations in the policeman's health, we have carried out a research/intervention program with workers of a given company of the 1st Batallion of the Military Police of Espírito Santo. From the obtained data we have been able to notice that police work is characterized by the extension of the work activity to all the scopes of the worker's life, moving through it not only with a given institutional identification, but also with the conflicts and contradictions which distinguish the function of these workers, causing great mental suffering; mental suffering such that is worsened by the lack of spaces for its collective analysis in the military institution.